Comparison of clinical and pathological characteristics between early gastric cardiac cancer and early gastric non-cardiac cancer - Yu, Bin; Wu, Hong-Lei; Li, Shuai; Tao, Dao-Yu; Zuo, Zhen-Xiang; Qi, Xing; Zhang, Hui-Min (Frontiers in Oncology, 2025)
BackgroundPrevious studies primarily focused on advanced-stage gastric cancer have identified significant differences between gastric cardiac cancer (GCC) and gastric non-cardiac cancer (GNCC) in clinical, pathological, and molecular phenotypes. This study focuses on early-stage GCC and GNCC cases treated with Endoscopic Submucosal Dissection (ESD) to investigate differences in clinical presentation and case characteristics, thereby providing scientific evidence for early diagnosis and treatment strategies for gastric cancer.MethodsThis study retrospectively analyzed 304 patients, comprising 126 with early GCC and 178 with early GNCC. To further investigate the differences between the early GCC and early GNCC, 1:1 propensity score matching was applied, enabling a more rigorous comparison of the endoscopic and clinicopathological features between the two cohorts. Patients were categorized based on tumor involvement in the deep submucosa (≥500 μm, SM2) and positive ESD margins. Multivariate analysis was conducted to identify independent risk factors for SM2 or deeper infiltration and incomplete resection.ResultsCompared to the early GNCC group (n = 178), the early GCC group (n = 126) had a higher proportion of older patients and males. After propensity score matching, early GCC cases (n = 112) exhibited a greater prevalence of moderately differentiated tubular adenocarcinoma, a lower prevalence of papillary carcinoma, a higher likelihood of SM2 or deeper infiltration, and an increased probability of positive margins after ESD (P < 0.05 for all comparisons). Gastric cardia location (odds ratio (OR) = 3.395, P = 0.031), larger tumor size (OR = 1.375, P = 0.006), and mixed-type adenocarcinoma (OR = 6.975, P < 0.001) were identified as independent risk factors for SM2 or deeper infiltration in early gastric cancer. In early GCC cases, moderately differentiated tubular adenocarcinoma (OR = 14.959, P = 0.035) and SM2 or deeper invasion (OR = 16.65, P < 0.001) were identified as independent risk factors for positive margins following ESD.ConclusionGCC and GNCC show notable differences in clinical and pathological characteristics, with GCC demonstrating higher invasiveness. Therefore, endoscopists should strengthen identification and intervention efforts for early-stage cancers in the cardia region to improve patient prognosis.